The Existence of Kaharingan Within Dayak Identity in West Kalimantan - Fahmi, Moch Riza; Muhyiddin, Asep (Pascasarjana IAIN Pontianak, 2023)
Identity is a fluid and adaptive phenomenon that suits the needs of its users. Identity is often used as a tool by certain groups for certain purposes, for example as a form of resistance or as a means to show the existence of a group. In West Kalimantan, the Kaharingan religion reveals its existence in the Dayak identity. This paper aims to explore the existence of the Kaharingan religion in the Dayak community in West Kalimantan, especially when there is a rift between ethnic groups. The rifts between ethnic groups in West Kalimantan are commonly referred to as social conflicts that occurred around the 1990s. This paper was based on literature research data using historical and phenomenological approaches. The historical approach was used to describe the history of the Dayak ethnicity, the Kaharingan religion and the history of social conflicts between 1997 and 1999 in West Kalimantan, while the phenomenological approach is used to analyze the phenomenon of the existence of the Kaharingan religion when social conflicts occurred. The results showed that the existence of the Kaharingan religion was on the rise during the 1997-1999 social conflicts among the Dayaks. The emergence of the Kaharingan religion could be seen in the rituals, such as the Nyaru Tariu, Mangkok Merah, and Tiwah ceremonies. Despite the fact that some of the Dayaks at that time were already Catholics and Protestants, they performed the rituals of the Kaharingan religion. After the 1997-1999 social conflicts, the Kaharingan Religion was institutionally declared on May 16, 2019 in Bengkayang Regency under the name of the Indonesian Kaharingan Religious Council (MAKI) West Kalimantan.